Beware of the purple peanut butter - Stine, R. L. (New York : Scholastic, 1996)
You get into the refrigerator and eat purple goop and you start to shrink and then you must make a choice of what to eat to get out of a mess.
"RL4"--p. [4] cover.
"A Parachute Press book"--T.p. verso.
"An Apple paperback."
008-012.
11 13 29 38
Keywords: Plot-your-own-stories.; Food -- Fiction; Monsters -- Fiction; Science -- Experiments -- Fiction; Plot-your-own-stories.